Implementation of Web-Based Dukcapil Ceiling Program in Improving Population Administration Services - Khoirunnisak, Khoirunnisak; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2024)
This study aimed to analyze the implementation of Dukcapil Web Plavon in improving population administration service in Glagaharum village. Descriptive research with a qualitative approach was conducted, using interviews, observations, and documentation as data collection techniques. T.B. Smith's theory was used to analyze four indicators: Policy Wanted, Target Targeted, Organizational Implementation, and Environmental Factors. The desired policy indicator showed that the program was implemented in accordance with the objectives set by the Civil Registration and Population Service. However, the target indicator revealed that many people still cannot use Dukcapil's Web Plavon. The organizational implementation indicator showed that socialization related to the existence and use of Dukcapil Web Platoon has not been maximized, causing a large number of people to not understand how to use it. The environmental factors indicator revealed barriers associated with frequent power outages, unstable internet connection, lack of printer, and lack of room cooling air conditioner. The study implies that the implementation of Dukcapil Web Plavon faces various challenges that need to be addressed to improve population administration service. Highlight : The study analyzed the implementation of Dukcapil Web Plavon in improving population administration services in Glagaharum Village using a qualitative approach The organizational implementation indicator revealed that the socialization of the program has not been maximized, leading to a lack of understanding among the people on how to use it Environmental factors such as frequent power outages, unstable internet connection, lack of printer, and absence of room cooling air conditioner were identified as barriers to the implementation of Dukcapil Web Plavon Keywords: Dukcapil Web Plavon, population administration, Glagaharum Village, implementation, challenges